2014
DOI: 10.1002/ijc.28963
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus DNA prevalence and type distribution in anal carcinomas worldwide

Abstract: Knowledge about the human papillomaviruses (HPV) types in anal cancers in some world regions is scanty. Here we describe the HPV DNA prevalence and type distribution in a series of invasive anal cancers and anal intraepithelial neoplasias (AIN) grades 2/3 from 24 countries. We analyzed 43 AIN 2/3 cases and 496 anal cancers diagnosed from 1986 to 2011. After histopathological evaluation of formalin-fixed paraffin-embedded samples, HPV DNA detection and genotyping was performed using SPF-10/DEIA/LiPA25 system (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
268
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 317 publications
(294 citation statements)
references
References 32 publications
14
268
1
11
Order By: Relevance
“…2,42 The 9vHPV vaccine may also provide increased protection against an extra ∼5% to 10% of vulvar, vaginal, and anal cancers and highgrade vulvar, vaginal, and anal intraepithelial neoplasia. 4,43,44 Prophylactic administration of a 3-dose regimen of 9vHPV vaccine to HPV-naive women aged 16 to 26 years is highly efficacious against vaccine HPV type-related infection and disease. 45 In this report we evaluated whether the 9vHPV vaccine induces noninferior serum antibody responses in boys and girls 9 to 15 years of age (the ideal prophylactic HPV vaccination population) compared with adolescent females/women (ie, young women) 16 to 26 years of age (the population used to establish 9vHPV vaccine efficacy).…”
Section: What This Study Addsmentioning
confidence: 99%
“…2,42 The 9vHPV vaccine may also provide increased protection against an extra ∼5% to 10% of vulvar, vaginal, and anal cancers and highgrade vulvar, vaginal, and anal intraepithelial neoplasia. 4,43,44 Prophylactic administration of a 3-dose regimen of 9vHPV vaccine to HPV-naive women aged 16 to 26 years is highly efficacious against vaccine HPV type-related infection and disease. 45 In this report we evaluated whether the 9vHPV vaccine induces noninferior serum antibody responses in boys and girls 9 to 15 years of age (the ideal prophylactic HPV vaccination population) compared with adolescent females/women (ie, young women) 16 to 26 years of age (the population used to establish 9vHPV vaccine efficacy).…”
Section: What This Study Addsmentioning
confidence: 99%
“…Alemany and co-authors [10] found that female patients constituted the majority of the cases of SCC (66.3%). Ouhoummanea and co-authors [8] found that the majority of incidence of anal cancer (60%) was in women.…”
Section: Discussionmentioning
confidence: 97%
“…Infection with oncogenic, or high-risk, HPV-16 was detected in all cases. Other studies also report that HPV-16 was the main HPV type found in over 80% of carcinomas [10,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations